1994
DOI: 10.1021/bi00167a032
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides of Campylobacter jejuni serotype O:19: Structures of core oligosaccharide regions from the serostrain and two bacterial isolates from patients with the Guillain-Barre syndrome

Abstract: Lipopolysaccharides from phenol-water extraction of cells of Campylobacter jejuni serotype O:19 were separated into a water-soluble gel of low M(r) and a water-soluble component of high M(r). Acetic acid hydrolysis of the ketosidic linkages to lipid A furnished respectively a core oligosaccharide, the structure of which is reported herein, and an O antigenic polysaccharide. Structural investigations were performed on the O-deacetylated lipopolysaccharide of low M(r), the liberated core oligosaccharide and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
163
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 27 publications
10
163
0
Order By: Relevance
“…This oligosaccharide residue clearly provides the structural basis for interaction with Ctxb. It should be mentioned that this terminal tetrasaccharide, Galβ1-3GalNAcβ1-4(NeuAcα2-3) Galβ1-4-with various degree of sialylation, has been previously reported in the LOS of HS 19 [36][37][38]. In the present study, we have further identified the same terminal core structure in strain HS 19 as the major component that is likely the antigenic epitope contributing to molecular mimicry in GBS.…”
Section: Discussionsupporting
confidence: 76%
“…This oligosaccharide residue clearly provides the structural basis for interaction with Ctxb. It should be mentioned that this terminal tetrasaccharide, Galβ1-3GalNAcβ1-4(NeuAcα2-3) Galβ1-4-with various degree of sialylation, has been previously reported in the LOS of HS 19 [36][37][38]. In the present study, we have further identified the same terminal core structure in strain HS 19 as the major component that is likely the antigenic epitope contributing to molecular mimicry in GBS.…”
Section: Discussionsupporting
confidence: 76%
“…Notwithstanding the mechanism involved, the higher level of Cj1121c activity may be relevant to the pathogenesis of C. jejuni because the glycosylation of proteins controlled by Cj1121c and the glycosylation of flagellins controlled by the cj1293 operon might be necessary at different stages during host colonization. Recently, it was reported that protein glycosylation was enhanced in C. jejuni in iron-depleted medium and that transcription of the pgl cluster 5 A. Merkx-Jacques, R. K. Obhi, and C. Creuzenet, unpublished data. Five days following oral inoculation with 10 6 cfu, viable counts were determined, and the detection limit was 60 cfu (log 10 1.78)/g.…”
Section: Discussionmentioning
confidence: 93%
“…Our ongoing efforts to characterize the biological function of Cj1294 indicate that it is necessary for the production of virulence factors. 5 However, the biochemical data exclude the possibility that Cj1294 would exert this effect through the production of DAB, a sugar necessary for protein glycosylation in C. jejuni (19). Hence, the aminotransferase enzyme responsible for DAB biosynthesis remains to be identified.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, an LPS containing an epitope similar to GM1b was identified from C. jejuni isolated from a GBS patient with high anti-GM1b antibody titers (101). C. jejuni strains isolated from patients with Miller-Fisher syndrome had an LOS epitope mimicking GQ1b, GT1a, or GD3 (11,67,97). Isolates from patients with GBS more frequently had a GM1-like epitope than did isolates from patients with Miller-Fisher syndrome.…”
Section: Oligosaccharides Of Lpss That Mimic Ganglioside Structuresmentioning
confidence: 99%